Transitional justice : global mechanisms and local realities after genocide and mass violence - Hinton, Alexander Laban (Genocide, political violence, human rights series., 2010)
"The origins of this project date back to a 2007 symposium, 'Local justice : global mechanisms and local meanings in the aftermath of mass atrocity, ' held at Rutgers University--Newark [N.J.] ... Several participants later presented papers in a session at the July 2007 meeting of the International Association of Genocide Scholars, which was held in Bosnia and Herzegovina."--Acknowledgments